Analisis Yuridis Terhadap Tindak Pidana Penyalahgunaan Wewenang oleh Anggota DPRD Dalam Pengawasan Pelaksanaan Peraturan Daerah (Studi Pada Kantor DPRD Labuhan Batu) - Sahbudi Sahbudi; Akiruddin Ahmad; Mahmuddin Hasibuan (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyze the abuse of authority by members of the Regional House of Representatives (DPRD) in exercising the supervisory function over Regional Regulations in Labuhanbatu Regency from the perspective of administrative law. The study focuses on the legal framework governing DPRD authority, forms of misuse of authority in the implementation of supervisory functions, and mechanisms of accountability and prevention. This research employs an empirical legal research method using statutory and conceptual approaches. Data were obtained through interviews with relevant parties within the Labuhanbatu DPRD and document analysis of legal regulations and supporting documents. The results show that DPRD supervisory authority is legally regulated through the Regional Government Law, Government Administration Law, the Law on the People's Consultative Assembly, House of Representatives, Regional Representative Council, and Regional House of Representatives (MD3 Law), as well as regulations on corruption eradication. However, the implementation of supervision still faces gaps between legal norms and practices, particularly regarding the potential politicization of supervisory functions, conflicts of interest in budgeting processes, lack of objectivity in oversight, and inadequate control over the implementation of DPRD members’ constituency aspiration programs. Prevention of authority abuse is carried out through strengthening the DPRD Ethics Council, improving members’ capacity, implementing technology-based transparency, and increasing public participation. This study confirms that the effectiveness of DPRD supervision is influenced not only by regulations but also by institutional integrity, legislative capacity, and public accountability mechanisms.